(untitled) (Filologia e Linguística Portuguesa, 2005)
This paper explains the idea of persisting phonic features, from a speech variety found in the Bandeirante trail. The observation focus translated into the phonetic articulation and acoustic perception ensuing from the pronunciation of the <lh> digraph.